Phloroglucinol Degradation in the Rumen Promotes the Capture of Excess Hydrogen Generated from Methanogenesis Inhibition - Martinez-Fernandez, Gonzalo; Denman, Stuart E.; Cheung, Jane; McSweeney, Christopher S. (Frontiers in Microbiology, 2017)
Strategies to manage metabolic hydrogen ([H]) in the rumen should be considered when reducing ruminant methane (CH4) emissions. However, little is known about the use of dietary treatments to stimulate rumen microorganisms capable of capturing the [H] available when CH4 is inhibited in vivo. The effects of the phenolic compound phloroglucinol on CH4 production, [H] flows and subsequent responses in rumen fermentation and microbial community composition when methanogenesis is inhibited were investigated in cattle. Eight rumen fistulated Brahman steers were randomly allocated in two groups receiving chloroform as an antimethanogenic compound for 21 days. Following that period one group received chloroform + phloroglucinol for another 16 days, whilst the other group received only chloroform during the same period. The chloroform treatment resulted in decreased CH4 production and an increase in H2 expelled with a shift in rumen fermentation towards higher levels of propionate and formate and lower levels of acetate at day 21 of treatment. Bacterial operational taxonomic units (OTUs) assigned to Prevotella were promoted whilst Archaea and Synergistetes OTUs were decreased with the chloroform treatment as expected. The shift towards formate coincided with increases in Ruminoccocus flavefaciens, Butyrivibro fibrisolvens and Methanobrevibacter ruminantium species. The addition of chloroform + phloroglucinol in the rumen resulted in a decrease of H2 expelled (g) per kg of DMI and moles of H2 expelled per mol of CH4 decrease compared with the chloroform only treated animals. A shift towards acetate and a decrease in formate were observed for the chloroform + phloroglucinol-treated animals at day 37. These changes in the rumen fermentation profile were accompanied by a relative increase of OTUs assigned to Coprococcus spp., which could suggest this genus is a significant contributor to the metabolism of this phenolic compound in the rumen. This study demonstrates for the first time in vivo that under methanogenesis inhibition, H2 gas accumulation can be decreased by redirecting [H] towards alternative sinks through the nutritional stimulation of specific microbial groups. This results in the generation of metabolites of value for the host while also helping to maintain a decreased H2 partial pressure in the methane-inhibited rumen.